Coating material, coating method for coating material, and coating film structure
The coating material with non-true sphere aggregate components addresses adhesion and safety issues in existing technologies, resulting in a safer, durable, and stain-resistant finish.
Patent Information
- Application Number
- JP2023092382
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-05
- Publication Date
- 2024-12-17
AI Technical Summary
Existing coating materials using glass beads as aggregate components face issues with adhesion, leading to sand falling and safety hazards during application, as well as potential sharp edges causing dirt accumulation and surface damage.
A coating material composed of synthetic resin and non-true sphere aggregate components with specific particle sizes and bulk specific gravities, lacking sharp corners, to ensure better adhesion and reduce sand falling, while maintaining a safe and durable finish.
The solution provides a coating film with reduced sand falling, improved safety, and enhanced resistance to staining, achieving a visually appealing and durable finish.
Smart Images

Figure 2024174520000001 
Figure 2024174520000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a coating material containing an aggregate component for use on the walls of structures such as buildings, and to a coating method and coating film structure that utilize this coating material. [Background technology]
[0002] Conventionally, various coating materials have been used for surface decoration of walls of buildings and other structures. For example, there are stone-like coating materials made of synthetic resin and colored aggregate, which are widely used due to the texture such as colorfulness of the resulting coating film. There are also coating materials made from crushed or processed materials such as glass or ceramics, and by using these coating materials to decorate the surface of structures, it is possible to obtain a finish with a good texture.
[0003] The crushed glass and ceramics are mainly obtained by simply crushing recycled materials and adjusting the particle size, and for processed glass and ceramics, spherical beads are often used because they can be produced efficiently using this manufacturing method. A representative example is the coating material described in JP-A-2001-106979.
[0004] This coating material is prepared by mixing a base paint with glass beads having an average particle size of 0.3 to 0.5 mm and glass beads having an average particle size of 1.0 to 2.0 mm, and it is described that this coating material presents an appearance with excellent design, allows for simple application work, and realizes a coating film of uniform thickness. This is because, of the two types of glass beads, the glass beads with the larger average particle size are extremely slippery when the topcoat is applied with a trowel, as the surface of the trowel comes into contact with the smooth surface of the glass beads and can move easily, making the application process extremely easy.
[0005] It exerts a spacer effect that allows a uniform coating film to be formed between the glass beads, which helps to form a coating film of uniform thickness. The small particle glass beads fill the gaps between the larger glass beads to prevent their aggregation, disperse the larger glass beads, and support the spacer effect. They also fill the gaps between the larger glass beads to prevent the coating from shrinking due to drying, which is effective in ensuring the uniformity of the coating. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2001-106979 A Summary of the Invention [Problem to be solved by the invention]
[0007] However, although such coating materials produce a good finish, the use of glass beads makes it difficult for the synthetic resin, which is the binder component of the coating material, to adhere to the glass beads, and as a result, many of the glass beads that do not adhere to the wall or other object being coated during the coating process fall at the feet of the worker, and these spherical glass beads can cause the worker to slip.
[0008] Furthermore, if a lot of sand falls, it may not be possible to achieve the desired design or it may be difficult to achieve the desired design. This is because the surface area of beads such as glass beads is small, and the shape of the beads makes it difficult for the binder component to adhere to the surface.
[0009] Furthermore, in the case of crushed glass or ceramics, the surfaces tend to be angular compared to bead-shaped materials, and due to this shape, the binder components tend to adhere to the surface more easily, reducing the amount of sand that falls off, making it easier to obtain the desired design. However, if the shape of the crushed material has sharp angles either partially or entirely, the crushed material may pierce the worker during the coating process.In addition, the sharp edges of the crushed material may be exposed on the surface of the coating material that is finished.
[0010] In that case, the sharp edges of the finished surface can easily catch on dirt, and the crushed material can get stuck in your hand when you touch it. The present disclosure provides a coating material that reduces sand fall, makes it easy to obtain a desired finish, is resistant to dirt, and can provide a safe finish. [Means for solving the problem]
[0011] This coating material is composed primarily of synthetic resin and aggregate components, characterized in that the aggregate components are non-spherical and free of acute angles, have particle diameters in the range of 45 μm to 2000 μm, and have bulk density in the range of 1.0 to 2.0. This reduces sand fall, makes it easier to obtain the desired finish, makes it difficult for dirt to stick, and provides a safe finished surface.
[0012] The aggregate component is transparent crushed glass and contains coloring components finer than the crushed glass, so that a better finished surface can be obtained. The thickness of the coating film formed by the coating material containing aggregate components is in the range of 0.05 to 3.00 mm, and by forming an uneven shape within this thickness range, sand falling is reduced and the desired finish can be easily obtained, and the finished surface is resistant to dirt and safe.
[0013] A better finished surface can be obtained by applying a coating material containing aggregate components after a colored layer has been formed on the object to be coated. A better finished surface can be obtained by laminating a colored layer and a coating layer formed from a coating material containing aggregate components. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] The present disclosure relates to a coating material whose main components are synthetic resin and aggregate components, characterized in that the aggregate components are non-spherical and free of acute angles, have particle diameters in the range of 45 μm to 2000 μm, and have bulk specific gravity in the range of 1.0 to 2.0.
[0015] The coating material of the present disclosure is composed primarily of synthetic resin and aggregate components, and the synthetic resin components bond the aggregate components described below and other fillers and additives to form a coating film, and are an important component for adhering the coating film to the object to be coated. This synthetic resin is capable of forming a transparent film after it has hardened and dried. By becoming transparent, the color tone and texture of the aggregate components can be seen in the coating film, making it possible to obtain a coating film with good design.
[0016] Examples of the synthetic resin include acrylic resin, styrene resin, urethane resin, silicone resin, fluororesin, epoxy resin, melamine resin, alkyd resin, vinyl chloride resin, vinyl acetate resin, polyester resin, and the like, either alone or as a copolymer. Further, the resin may be dissolved in an organic solvent, dispersed in water as an emulsion, or dispersed in a weak solvent.
[0017] Of these, synthetic resin emulsions are often used because they are easy to obtain, the resulting clear paint is easy to handle, the viscosity can be adjusted with water, and it is easy to obtain a relatively thick coating film. This synthetic resin emulsion is a general one that can be produced by a common polymerization technique such as emulsion polymerization, and includes synthetic resin emulsions produced from the synthetic resins described above.
[0018] From the viewpoints of suitability as a coating material, physical properties, ease of availability, and durability such as weather resistance of the clear film, acrylic synthetic resin emulsions made from acrylic resin and styrene resin, and acrylic-styrene synthetic resin emulsions are preferably used. In order to further improve weather resistance, urethane-based synthetic resin emulsions, silicone-based synthetic resin emulsions, fluorine-based synthetic resin emulsions, acrylic silicone-based synthetic resin emulsions, etc. may be used.
[0019] It is preferable that the synthetic resin emulsion has good drying properties, and the film thickness of this coating material is preferably in the range of 0.05 mm to 3.0 mm, and within this thickness range, it often forms an uneven shape and becomes a relatively thick film. Therefore, if the drying property is poor, when it rains after application, the applied material may run off if it is not yet hardened or dried.
[0020] The glass transition temperature of the synthetic resin is preferably in the range of -10 to 40°C. If the temperature is lower than -10°C, the coating film formed may be easily soiled, and if the temperature is higher than 40°C, the coating film may be easily cracked. A synthetic resin with an appropriate glass transition temperature can be selected depending on the target substrate, etc. Next, the aggregate component, which is an important element of the present disclosure, has a particle size in the range of 45 μm to 2000 μm and a bulk density in the range of 1.0 to 2.0.
[0021] In addition, the shape of the aggregate component is non-spherical and has no sharp edges. By using this, it is possible to obtain a finished surface that is safe, with less sand falling out, and is easier to achieve the desired finish and less susceptible to dirt. One specific shape of this non-spherical aggregate component that has no sharp angles is a polyhedron with four or more sides composed of straight edges connecting multiple vertices and faces surrounded by those edges, where the boundaries of the faces are straight lines and the dihedral angles between adjacent faces are in the range of 90° to 180° and account for more than 50% of the surface of the aggregate component.
[0022] Aggregate components that are non-spherical in shape and free of sharp edges can be obtained by crushing glass or ceramic products and removing the sharp edges. In a typical manufacturing method, glass, ceramics, and other products are crushed in a crusher. The crushed material is then sifted to adjust the particle size and remove impurities. The adjusted particle size is then further crushed using crushing beads to remove any sharp edges.
[0023] In this way, the aggregate component used in the present disclosure can be obtained. This aggregate component has few sharp edges, so it can be used safely, and the coating material using this aggregate component does not pierce the worker during application. Furthermore, the coating film formed thereby is less likely to accumulate dirt and is not susceptible to puncture by ground material when touched.
[0024] Since the aggregate component is made of glass or ceramic, it is stable and does not deteriorate due to light or oxygen, and the coating film made using this coating material is less likely to discolor. The particle size of this aggregate component is in the range of 45 μm to 2000 μm, which makes it easy to obtain the desired finish.
[0025] If the particle size is smaller than 45 μm, it becomes difficult to remove sharp corners using grinding beads, and the fluidity becomes poor when mixed with a coating material. If the particle size is larger than 2000 μm, the aggregate components may be too large and it may be difficult to obtain the desired finish. The particle size is a value obtained by mechanical sieving using a metal mesh sieve specified in JIS Z8801-1:2019.
[0026] The bulk density of the aggregate component is in the range of 1.0 to 2.0, and if it is smaller than this range, the specific gravity of the coating material itself will be small, making it difficult to apply the coating and to obtain the desired finish. Conversely, if it is larger, a lot of sand may fall out. The bulk density is a value obtained by the unit volume mass testing method described in JIS A1104:2019.
[0027] In addition to the synthetic resin and aggregate components, additives and pigment components can be added to this coating material. The additives include various additives that are generally mixed into paints, such as defoamers, dispersants, wetting agents, film-forming agents, antifreeze agents, thickeners, preservatives, algae inhibitors, fungicides, and pH adjusters, as needed. It is also preferable to add additives capable of improving the weather resistance of the coating film, such as light stabilizers, ultraviolet absorbers and antioxidants, and these may be used alone or in combination of two or more kinds.
[0028] The light stabilizer captures free radicals that affect the deterioration of the coating film, the ultraviolet absorber absorbs harmful ultraviolet rays and converts them into harmless heat or kinetic energy, and the antioxidant prevents thermal oxidative deterioration of the coating film. The coloring components of the present disclosure include colored aggregates, color pigments, dyes, etc., and are preferably added to impart color to the formed coating film.
[0029] The coloring component is preferably finer than the aggregate component, and when the coloring component is used, the aggregate component is preferably transparent crushed glass, which allows a better finished surface to be obtained. In this way, by using a transparent crushed glass aggregate as the aggregate component and adding a coloring component, the color tone of the coating film can be more clearly confirmed, and it is possible to obtain a coating film in which the color tone stands out.
[0030] Among these coloring components, it is preferable to use colored aggregate, which can provide a better finish. The colored aggregate may be a highly transparent aggregate, a highly opaque aggregate, a glossy aggregate, a non-glossy aggregate, etc. A completely colorless and transparent aggregate is not a colored aggregate because it has no color.
[0031] Colored aggregates include crushed colored natural stone and crushed ceramics, etc. Colored aggregates are also available, which are artificially colored crushed colored natural stone or ceramics. Examples of crushed colored natural stones include crushed marble particles such as granite, serpentine, obsidian, fluorite, canary, white jade, kansui stone, small cherry blossom, urushi snow, Minokasumi, and serpentine, as well as silica sand and natural fine gravel.
[0032] Further examples include lightweight aggregates such as shirasu balloons, perlite, and foamed crushed glass. In addition to the above components, it is also possible to add components such as aluminum hydroxide as a colored aggregate, and flame retardants such as halogen-based, phosphorus-based, and antimony trioxide-based compounds. Among these colored aggregates, colored aggregates are preferably used. Many of these colored aggregates are made by crushing aggregates such as kansui stone or silica sand and coloring them. Compared to crushed natural stone, color, grain size, and particle size are stable, so by using them, the color of the coating film formed by the coating material can be made more stable.
[0033] Furthermore, the coating operation is stable and the coating stability is excellent. In particular, artificially colored silica sand and kansui stone are more preferably used since they are easily available and have excellent miscibility with synthetic resins.
[0034] In most coloring methods, silica sand or kansui stone is placed in a container, and while stirring using a mixer or other device, paint, pigment, glaze, etc. is sprayed evenly over the aggregate using a sprayer or other device to color the aggregate. Once the aggregate has been uniformly colored, it is then dried using hot air or other means while vibrating it in a vibration dryer. The particle size of the colored aggregate is smaller than that of the aggregate component, and is preferably in the range of 37 μm to 800 μm. If the aggregate is finer than 37 μm, the colored aggregate loses its colorfulness, and the stability of the coating material and the workability of the coating work may be deteriorated.
[0035] In addition, the coating film that is formed may crack due to shrinkage, and the colored aggregate may lack variety, resulting in a lack of design appeal. In the case of aggregate larger than 800 μm, the balance with the aggregate component (ground glass) becomes poor, which may result in inferior design.
[0036] The ratio of the colored aggregate to the aggregate components is preferably in the range of 2:1 to 1:5 by weight, and within this range, it is possible to obtain a coating film that fully expresses the transparency of the crushed glass aggregate component and the color and variety of the colored aggregate. Other coloring components include color pigments and dyes, and color pigments are often used in paints because of their weather resistance and additive amount.
[0037] As the coloring pigment, inorganic pigments, organic pigments or both may be used, and those having good weather resistance are preferred. The coloring pigments that can be used include those commonly used for coloring paints, such as titanium oxide, carbon black, yellow iron oxide, red iron oxide, cyanine blue, and cyanine green, and liquid coloring pigments are often used due to their ease of handling.
[0038] The color of color pigments and dyes often changes significantly depending on the amount added, and since it is often difficult to adjust the amount added, diluted color pigments and dyes are sometimes used. Colored paints can also be used. When using paints, it is often difficult to adjust the color with pigments, such as when the desired color is a light color such as gray or cream.
[0039] One or more of these coloring components may be used, and this is preferably done to stabilize the color of the coating film. In the coating material of the present disclosure, the ratio of the synthetic resin to the aggregate, which is a combination of the aggregate component and the colored aggregate, is: The weight ratio is preferably in the range of 1:0.8 to 1:10. If the weight ratio is less than 1:0.8, the aggregate components and colored aggregate may separate during storage, depending on the viscosity of the coating material.
[0040] If the aggregate ratio is more than 1:10, the synthetic resin content will be low and the coating film may become brittle. Also, if there is too much aggregate or colored aggregate, the viscosity of the coating material will tend to increase, making it difficult to mix and making it impossible to obtain a uniformly mixed coating material. More preferably, the weight ratio of the synthetic resin to the aggregate, which is the aggregate component and the colored aggregate, is in the range of 1: 2 to 1: 5. Within this range, separation during storage is small and the coating film does not become brittle.
[0041] The coating material thus constructed can be obtained by mixing and dispersing the respective constituent materials. The method of mixing and dispersing is not particularly limited, and can be carried out using a mixer such as a general mixer. The coating material disclosed herein is applied by conventional painting methods using tools such as spray painting, painting rollers, brushes, and trowels to form a coating film.
[0042] Spray painting allows large areas to be painted quickly, and as a paint gun for spray painting the coating material of the present disclosure, a lysine gun or a tile gun, which can paint a coating material containing relatively coarse aggregate, is preferred. By using a coating roller for coating, the desired film thickness and unevenness can be easily achieved.
[0043] The painting roller becomes a painting roller capable of painting by attaching a painting roller cover, which is composed of a cylindrical member and a fibrous or sponge-like paint retaining layer, to a roller tool. When applying the coating material of the present disclosure with a painting roller, it is preferable to use a long-haired wool roller with a paint-retaining layer having a pile length of 20 mm or more, a spongy sponge roller, or a sand-bone roller, since these rollers enable a relatively large amount of coating to be applied.
[0044] The coating film formed by this coating material has a thickness in the range of 0.05 mm to 3.0 mm due to the aggregate component, which is the main component, in the range of 45 μm to 2000 μm, and it is preferable that unevenness is formed within this thickness range. This uneven coating film can easily impart a voluminous finish to the object being coated, and the finished surface is resistant to dirt and safe.
[0045] The coating material of the present disclosure preferably has an aggregate component that is transparent ground glass, and contains coloring components that are finer than this ground glass, thereby making it possible to obtain a more three-dimensional and excellent finished surface. This is because the coating film made from the coating material contains crushed glass, which is an aggregate component, and the coating film has a three-dimensional appearance due to the difference in hiding power depending on the thickness of the coating film.
[0046] In other words, a large amount of crushed glass particles gather in thicker parts of the coating film, while there is less crushed glass in thinner parts of the coating film. As a result, the hiding power of the coating film changes depending on the thickness of the coating film, resulting in different colors. In the present disclosure, it is further preferable to coat the object with a coating material containing an aggregate component after forming a colored layer on the object to be coated, thereby obtaining a better finished surface.
[0047] This colored layer can be formed by simply utilizing an existing layer on the object to be coated, or by attaching a colored sheet-like material or by applying paint, and the method of formation is not limited as long as it can be applied with the coating material of the present disclosure. Among these, paint is often used to form the colored layer, and the required color can be adjusted using inorganic pigments such as iron oxide or organic pigments. Any material that has good adhesion to the surface to be coated and also has good adhesion to the coating material is sufficient. Since the coating film made from the coating material of the present disclosure has thin parts, a material with excellent durability, such as weather resistance, is preferred.
[0048] The paint that forms this colored layer may be any of the types generally available on the market, and is generally composed of synthetic resin as its main component, and often contains pigments and additives that are generally compounded into paints, such as defoamers, dispersants, wetting agents, film-forming aids, antifreeze agents, thickeners, preservatives, anti-algae agents, anti-fungal agents, pH adjusters, etc. For this synthetic resin, a general synthetic resin emulsion that can be produced by a common polymerization technique such as emulsion polymerization is often used, and water-based paints that use this as a binder are often used, resulting in better adhesion and durability.
[0049] In addition, by including one or both of a white pigment and a filler component, a relatively thick colored layer can be formed, and the color of the base and slight unevenness can be hidden, resulting in a better finish. These white pigments include titanium oxide and zinc oxide, and are primarily used to hide the color of the base and achieve a good finish, while extender pigments include calcium carbonate, diatomaceous earth, kaolin, talc, clay, bentonite, white carbon, aluminum hydroxide, and silica sand.
[0050] The average particle size of the extender pigment is often 150 μm or less, and calcium carbonate, diatomaceous earth, aluminum hydroxide and silica sand are preferably used because they are readily available. The content of these pigments such as white pigment and extender pigment is preferably in the range of 10 to 80% by volume of the pigment in the paint, and more preferably in the range of 30 to 70%.
[0051] If the pigment volume concentration is less than 10%, the hiding power of the coating film formed by the paint will decrease, and if it exceeds 80%, the amount of resin in the coating film will be low, which may affect durability and finish. Therefore, the pigment volume concentration is adjusted as necessary within this range, but by adjusting it to the range of 30 to 70%, a better finish will be achieved.
[0052] If it is less than 30%, it will be difficult to make unevenness in the base less noticeable, and if it exceeds 70%, the finish may be poor. In addition, the paint used to form the colored layer can also be used to form the colored layer in an uneven shape, thereby improving the adhesion of the coating material of the present disclosure.
[0053] When this colored layer is formed by paint, it is applied by the usual painting method such as spray painting, or by using tools such as a painting roller, brush, or trowel to form the colored layer. Among these, a painting roller is often used, which makes it easy to create unevenness in the colored layer.
[0054] This type of painting roller is similar to that described above, and is preferably used because the paint retention layer can be applied in a relatively large amount by using a long-haired wool roller with a pile length of 20 mm or more, a spongy sponge roller, or a sand rib roller, and a bumpy colored layer can be easily formed. The coating material disclosed herein is applied to a surface to be coated, and can be applied to a variety of objects, such as concrete, mortar, ALC panels, siding boards, extruded panels, gypsum boards, slate, ceramic, plastic, wood, stone, tiles, and the like, that make up the walls of buildings.
[0055] The coating material of the present disclosure, which is composed of these, will be described in more detail in the following detailed embodiment. First, the coating material is prepared. This coating material is prepared by preparing a vehicle containing a synthetic resin and then mixing it with an aggregate component. The vehicle used an acrylic synthetic resin emulsion with a glass transition temperature of 0°C and a solid content of 50%. Additives used included a film-forming agent, an antifoaming agent, a dispersant, a wetting agent, and a thickener. An example of the vehicle formulation is shown below.
[0056] Vehicle formulation examples Acrylic synthetic resin emulsion 420.0g Film-forming agent 50.0g Defoamer 3.0g Dispersant 1.5g Wetting agent 1.0g Thickener 1.5g Water 23.0g Total 500.0g Various aggregate components were added to this vehicle to prepare the coating material. The formulation is shown in Table 1.
[0057] [Table 1]
[0058] Shattered glass A and C were made by shattering transparent glass products and processing them to remove any sharp corners, and did not hurt when held in the hand. Shattered glass B was made by shattering transparent glass products and not processing them to remove any sharp corners, and it hurt when held in the hand. These crushed glass materials had a bulk density of 1.5. Crushed glass materials A and B passed through a metal mesh sieve with openings of 10 mesh and were retained on a 70 mesh sieve, while crushed glass material C was retained on a 10 mesh sieve.
[0059] The glass beads were general-purpose beads used as a filler for paints, and because they were spherical, they did not hurt when held in the hand. Glass beads A passed through a 10-mesh sieve and were retained on a 70-mesh sieve, while glass beads B passed through a 325-mesh sieve. The perlite used here is a general-purpose type used as a filler for paints; it is spherical in shape so that it does not hurt when held in the hand; it has a bulk density of approximately 0.1; and it passes through a 10-mesh sieve and is retained on a 50-mesh sieve.
[0060] The kansui stone used was a general-purpose type used as a filler for paints, and had passed through a sieve with 150 mesh openings. The colored sand was silica sand colored with acrylic resin enamel paint, and the sand that passed through a 70 mesh sieve and was retained on a 200 mesh sieve was used.
[0061] The coating materials were made by mixing and stirring the formula shown in Table 1 with a dissolver. The formula for coating material 7 was difficult to mix because the bulk density of perlite was low, which increased the bulk of the perlite. The formula for coating material 6 was difficult to mix, probably because the particle size of the glass beads was small, and the resulting coating material did not have much fluidity.
[0062] The prepared coating material was applied to the siding board as the coating surface using a sand-bone roller to a coating thickness of about 2 mm, and workability and finish were confirmed. For the colored layer, an acrylic resin-based flexible coating material with a pigment volume concentration of 60% was applied with a long-haired wool roller. We also checked the results of painting with a colorless and transparent acrylic resin primer. The results are shown in Table 2.
[0063] [Table 2]
[0064] When we checked the workability of the coating materials, Coating Materials 3 and 4 were not very good in workability because the crushed glass in the aggregate component sometimes got caught in the roller. Coating Material 5 caused a lot of glass beads in the aggregate component to fall off. Coating material 6 had poor fluidity and was difficult to apply. Coating material 8 had a small amount of perlite sand falling off.
[0065] The finish was visually inspected, and specifications 1 to 3 and 5 had a good finish. In particular, specification 3, which was coated with a colored layer of acrylic resin-based flexible coating material, had an uneven surface formed by the colored layer, resulting in a good finish with a more voluminous feel. Specification 6 did not have a good finish, probably because the aggregate component used in coating material 4 was large. Specification 4 and Specification 9 did not have crushed glass in the aggregate component used in the coating material, so compared to Specification 3, the coating film did not have much shading and the finish was not very good.
[0066] In terms of the feel of the coating, specification 5, which used coating material 3, whose aggregate component contains crushed glass that has not been treated to remove sharp edges, was painful to the touch. The staining property was evaluated by exposing each coating to the outdoors for one year and visually checking the staining of the coating. The coating of coating of specification 5 had stains caught on the aggregate components and was stained more than the other coatings.
Claims
1. The coating material is mainly composed of a synthetic resin and an aggregate component, and is characterized in that the aggregate component is non-spherical and has no acute angles, has a particle size in the range of 45 μm to 2000 μm, and has a bulk density in the range of 1.0 to 2.
0.
2. The coating material contains a transparent crushed glass aggregate component and a coloring component that is finer than the crushed glass.
3. A coating method for forming a coating film with a thickness of 0.05 mm to 3.0 mm using the coating material according to claim 1 or 2, the thickness of which is within the range of 0.05 mm to 3.0 mm, and which forms unevenness within the thickness range.
4. A method for applying a coating material, which comprises forming a colored layer on an object to be coated and then applying the coating material according to claim 1 or 2.
5. A coating film structure comprising a colored layer and a coating layer formed from the coating material according to claim 1 or 2 laminated thereon.
Citation Information
Patent Citations
Coating material and method for finishing the same
JP2001106979A
